The Mageburan Tradition and the Context of Social Studies Learning in Elementary School - Komang Surya Adnyana (Jurnal Pedagogi dan Pembelajaran, 2025)
Mageburan's local traditions and practices are not merely cultural or spiritual, they are deeply rooted in the community's history and identity. They can be viewed from a pedagogical perspective and contribute to the internalization of learning values, particularly in social studies education at the elementary school level. The purpose of this study is to analyze and provide an explanation of the nature of the mageburan tradition’s implementation, while also interpreting the values, social character, and social science learning dimensions that can be actualized in the pedagogical practice of elementary school level. The research method applied in this study is qualitative, within the framework of a single case study. Data collection methods were carried out through observation and interviews. Data analysis techniques used qualitative descriptive analysis. The research findings indicate that the mageburan tradition in social studies learning in elementary schools contributes to social recognition and balance. Furthermore, social wisdom tools (ethics of wisdom) can be utilized. These cultural practices can serve as a social arena for internalizing the values of gender equality in social studies learning in elementary schools. The mageburan tradition, as a subject of study in social studies learning at the elementary school level, contributes cognitively, affectively, psychomotorically, and non-disruptively to student development.